2013
DOI: 10.1007/s13595-013-0283-y
|View full text |Cite
|
Sign up to set email alerts
|

Understory dynamics after disturbance accelerate succession from spruce to beech-dominated forest—the Siggaboda case study

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
5
27
0
Order By: Relevance
“…It is to note that spruce is more vulnerable to heat and drought events because of its shallow root system (Schmid 2002;Bolte et al 2014) and its adaptation to cold and humid climate (Latołowa & van der Knaap 2006). Therefore an increasing proportion of beech is to expect in future at many sites in the Central European region (Menšík et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is to note that spruce is more vulnerable to heat and drought events because of its shallow root system (Schmid 2002;Bolte et al 2014) and its adaptation to cold and humid climate (Latołowa & van der Knaap 2006). Therefore an increasing proportion of beech is to expect in future at many sites in the Central European region (Menšík et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of such impacts is becoming available, as for example, Scots pine has declined in areas close to its dry distribution limit (Rigling et al 2013), beech forests recently showed growth depressions in Belgium (Kint et al 2012) and lost habitats in mountainous forests in Spain (Penuelas et al 2007), whereas the species expands its range following storm disturbances at its Northern range margin (Bolte et al 2014). At the European scale, there are signals of a trend change in increment ) and increased disturbance damage due to climate change (Seidl et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of admixture on root attributes also support the notion of a different belowground strategy between both species. This effect together with the discrepancies observed at the twig level, could be an additional evidence of the negative consequences of admixing Norway spruce trees within a group of European beech at early developmental stages (Bolte et al 2014).…”
Section: Response Of Growth To Admixture and Co 2 Enrichmentmentioning
confidence: 75%